Mechanism of femtosecond laser nano-ablation for metals - Hashida, M.; Miyasaka, Y.; Shimizu, M.; Ogata, T.; Sakagami, H.; Tokita, S.; Sakabe, S. (ALT Proceedings, 2026)
Metals have three ablation threshold fluences (high,middle and low-threshold fluence, here called) forfemtosecond laser pulses. In order to investigatethe physics of metal ablation under an intenseoptical field, the ions emitted from a laserirradiatedcopper surface were studied by time-offlightenergy spectroscopy. The low laser fluenceat which ions are emitted, Fth,L is 0.028 J/cm2, andtwo higher emission thresholds were identified atfluences of Fth,M =0.195 J/cm2 and Fth,H =0.470J/cm2. The relation between the number of emittedions per pulse Ni and laser fluence F was in goodagreement with Ni ∝F4 for Fth,L - Fth,M, Ni ∝F3 forFth,M - Fth,H, and Ni ∝F2 for ≥ Fth,H. Thedependence of ion production on laser energyfluence is explained well by multiphotonabsorption and optical field ionization.For fluence levels near the middle to high ablationthreshold, the formation of grating structures onmetal surfaces has been observed. The interspacesof grating structures were shorter than the laserwavelength, and the interspaces depend on fluencefor Mo and W with a 160 fs laser pulse. Thisphenomenon is well explained by the parametricdecay model proposed by Sakabe et al.